Providing Free Legal Services in Notarial Field Based on Notary Law Article 37 Paragraph (1) and (2) in Brebes Regency - Khairul Iman Susanto; Jawade Hafidz (Jurnal Akta, 2018)
The idea of a legal state demands the state administration and the government must be based on law and provide assurance of the basic rights of the people as stipulated in the law. Notary as a general official is appointed by the state, he/she does not receive honorarium from the State, but receives honorarium for legal services provided in accordance with his authority in accordance with Article 36 paragraph (2) of the UUJN. The purpose of this study was to analyze the meaning of article 37 paragraph (1) and (2) UUJN to notaries who provide legal services for free, to find and to analyze constraints in the application of article 37 paragraph (1) and (2) UUJN in providing services the law in the notary field to a poor person by a notary in Brebes Regency. The method used was empirical juridical and took location in Brebes Regency. The samples in this study were notary in Brebes Regency.Keywords: legal services; free; notary.